Analysis of waste to energy policy in different countries; Practices and implications for sustainable development - Kərimov, Elgün; Salmanov, Ceyhun (My University, 2024)
Based on an analysis of world experience, the practice of countries around the world, including Azerbaijan, and having statistical data, we can talk about the prospects for the development of this energy sector.Waste disposal is vital for humanity, primarily from an environmental point of view. There are various waste disposal methods depending on their type. The work describes in detail methods for processing waste and using it as energy and fertilizers. These methods are widely used in countries with developed economies, and in those countries that are not indifferent to the fate of the planet and humanity.
Keywords: Practice of developmend countries; Types and management of waste; Waste to energy policy; Renewable energy policy in Azerbaijan; The sustainable development of waste energy in Azerbaijan